2022
DOI: 10.1021/acs.jctc.2c00055
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Prediction of Nuclear Magnetic Resonance Parameters via the XYG3 Type of Doubly Hybrid Density Functionals

Abstract: Nuclear magnetic resonance (NMR) spectroscopy is one of the most powerful and versatile tools in elucidating molecular structures. To eliminate ambiguities of experimental assignments, accurate calculations of NMR spectra are of great importance. Here, a method for theoretical evaluation of the NMR shielding constants by analytic derivatives using gauge including atomic orbitals (GIAO) has been implemented for the XYG3 type of doubly hybrid density functionals (xDH), namely, the GIAO-xDH method. Benchmark calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…However, it is notable that none of these rms errors versus experiment is smaller than what is obtained from a PBE0 or B3LYP monomer correction (3.5–3.6 ppm), and two of the double-hybrid functionals give errors versus experiment that are slightly larger than results of the uncorrected GIPAW itself. The failure to obtain more accurate chemical shifts with the double-hybrid functionals is surprising, given previous studies that have demonstrated that double-hybrid functionals are more faithful to high-level benchmark absolute shielding constants (e.g., refs ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it is notable that none of these rms errors versus experiment is smaller than what is obtained from a PBE0 or B3LYP monomer correction (3.5–3.6 ppm), and two of the double-hybrid functionals give errors versus experiment that are slightly larger than results of the uncorrected GIPAW itself. The failure to obtain more accurate chemical shifts with the double-hybrid functionals is surprising, given previous studies that have demonstrated that double-hybrid functionals are more faithful to high-level benchmark absolute shielding constants (e.g., refs ).…”
Section: Resultsmentioning
confidence: 99%
“…These results are perhaps surprising, given that previous studies have found double-hybrid DFT, and MP2 absolute chemical shieldings reproduce high-accuracy benchmarks more faithfully than lower-level DFT functionals. It seems likely that considerable error cancellation is involved in the strong performance of basic hybrid functionals such as PBE0. Further evidence of error cancellation being involved comes from the work of Dračı́nský et al, who found that including spin–orbit and nuclear quantum effect corrections in their GIPAW + PBE0 results improved the accuracy of their 1 H chemical shifts relative to experiment, while decreasing the accuracy of their 13 C shifts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations